Exercise performance and symptoms in lowlanders with COPD ascending to moderate altitude: randomized trial - Furian, Michael (Int J Chron Obstruct Pulmon Dis, 2018)
OBJECTIVE: To evaluate the effects of altitude travel on exercise performance and symptoms in lowlanders with COPD. DESIGN: Randomized crossover trial. SETTING: University Hospital Zurich (490 m), research facility in mountain villages, Davos Clavadel (1,650 m) and Davos Jakobshorn (2,590 m). PARTICIPANTS: Forty COPD patients, Global Initiative for Obstructive Lung Disease (GOLD) grade 2–3, living below 800 m, median (quartiles) age 67 y (60; 69), forced expiratory volume in 1 second 57% predicted (49; 70). INTERVENTION: Two-day sojourns at 490 m, 1,650 m, and 2,590 m in randomized order. OUTCOME MEASURES: Six-minute walk distance (6MWD), cardiopulmonary exercise tests, symptoms, and other health effects. RESULTS: At 490 m, days 1 and 2, median (quartiles) 6MWD were 558 m (477; 587) and 577 m (531; 629). At 2,590 m, days 1 and 2, mean changes in 6MWD from corresponding day at 490 m were −41 m (95% CI −51 to −31) and −40 m (−53 to −27), n=40, P<0.05, both changes. At 1,650 m, day 1, 6MWD had changed by −22 m (−32 to −13), maximal oxygen uptake during bicycle exercise by −7% (−13 to 0) vs 490 m, P<0.05, both changes. At 490 m, 1,650 m, and 2,590 m, day 1, resting PaO(2) were 9.0 (8.4; 9.4), 8.1 (7.5; 8.6), and 6.8 (6.3; 7.4) kPa, respectively, P<0.05 higher altitudes vs 490 m. While staying at higher altitudes, nine patients (24%) experienced symptoms or adverse health effects requiring oxygen therapy or relocation to lower altitude. CONCLUSION: During sojourns at 1,650 m and 2,590 m, lowlanders with moderate to severe COPD experienced a mild reduction in exercise performance and nearly one quarter required oxygen therapy or descent to lower altitude because of adverse health effects. The findings may help to counsel COPD patients planning altitude travel. REGISTRATION: ClinicalTrials.gov: NCT01875133